Long-term evolution of comorbidities and their disease burden in individuals with and without HIV as they age: analysis of the prospective AGEhIV cohort study. Issue 3 (March 2023) - Verheij, Eveline; Boyd, Anders; Wit, Ferdinand W; Verboeket, Sebastiaan O; Verburgh, Myrthe L; van der Valk, Marc; Schim van der Loeff, Maarten F; Reiss, Peter; ,; Reiss, P.; Wit, F.W.N.M.; van der Valk, M.; et al.
Summary: Background: People with HIV generally have more ageing-associated comorbidities than those without HIV. We aimed to establish whether the difference in comorbidities and their disease burden changes with ageing. Methods: In this prospective, longitudinal cohort study, we assessed comorbidities commonly associated with ageing every 2 years in 596 HIV-positive and 550 HIV-negative participants. HIV-positive participants were recruited from the HIV outpatient clinic of the Amsterdam University Medical Centres (Amsterdam, Netherlands). HIV-negative participants were recruited from the sexual health clinic and the Amsterdam Cohort Studies at the Public Health Service of Amsterdam (Amsterdam, Netherlands). Inclusion criteria were participants aged 45 years or older and, for HIV-negative participants, a documented HIV-negative antibody test. The mean number of comorbidities present over time was compared between groups by use of Poisson regression, accounting for dropout and death through joint survival models. Mean disability-adjusted life-years (DALYs) accrued during 2-year intervals were compared between groups by use of an exponential hurdle model. Findings: Between Oct 29, 2010, and Oct 9, 2012, participants were enrolled and then prospectively followed up until their last visit before Oct 1, 2018. 1146 participants were followed up for a median 5·9 years (IQR 5·7–6·0), during which 231 participants (20·2%) dropped out: 145 (24·3%) of 596 HIV-positive and 86 (15·6%) of 550 HIV-negative. 38 (3·3%) of 1146 participants died: 31 (5·2%) of 596 HIV-positive and seven (1·3%) of 550 HIV-negative. 24 HIV-positive and two HIV-negative participants died from ageing-associated comorbidities. 15 HIV-positive participants versus one HIV-negative participant died from non-AIDS malignancies. At inclusion, mean number of comorbidities was higher in HIV-positive participants (0·65) than in HIV-negative participants (0·32; p<0·0001). Mean number of comorbidities increased at similar rates over time: rate ratio (RR) per year for HIV-positive participants 1·04 (95% CI 1·00–1·08), RR per year for HIV-negative participants 1·05 (1·01–1·08; pinteraction =0·78). Number of comorbidities was associated with an increased risk of death (hazard ratio 3·33 per additional comorbidity, 95% CI 2·27–4·88; p<0·0001). HIV-positive participants had higher increases in mean DALYs than HIV-negative participants (0·209 per year, 95% CI 0·162–0·256 vs 0·091 per year, 0·025–0·157; pinteraction =0·0045). This difference was reduced when deaths were excluded in establishing DALYs (0·127, 0·083–0·171 vs 0·066, 0·005–0·127; pinteraction =0·11). Interpretation: The larger comorbidity prevalence in HIV-positive participants aged 50–55 years on effective antiretroviral treatment than in HIV-negative participants increased similarly as participants aged and was associated with an increased risk of death, particularly of non-AIDS malignancies. Our findings reinforce the need for strategies to optimise prevention, screening, and early intervention. Funding: Netherlands Organization for Health Research and Development, Aidsfonds, Gilead Sciences, ViiV Healthcare, Janssen Pharmaceuticals, and Merck & Co. Translation: For the Dutch translation of the abstract see Supplementary Materials section.